PERAN INSTAGRAM SEBAGAI MEDIA UNTUK MEMPERKUAT LOYALITAS SUPPOTER PERSIJA DALAM KONTEKS SEPAK BOLA - Syaiful Bahri; Estu Widiyowati (Solidaritas, 2025)
Social media has become a strategic communication tool between football clubs and their supporters. Instagram, as a visual and interactive platform, is used by Persija Jakarta to convey information, build the club's identity, and strengthen emotional bonds with supporters, particularly the Jakmania community. This study aims to analyze Instagram's role in strengthening Persija Jakarta supporter loyalty. The method used was descriptive qualitative, with data collection techniques including observations of the official @persija account and in-depth interviews with active Jakmania members. The results show that Instagram contributes to shaping supporter loyalty across three main dimensions: cognitive, affective, and conative. The cognitive dimension is formed through consistent information about club activities. The affective dimension emerges through visual content that evokes emotion and closeness. Meanwhile, the conative dimension is evident in supporters' concrete actions in supporting the club, both online and offline. Intense digital interactions create a sense of belonging and solidarity among supporters. In conclusion, Instagram plays a significant role in building and strengthening Persija Jakarta supporter loyalty and is an effective tool for creating an emotionally connected supporter community in the digital era. Keywords: Instagram, Digital Communication, Supporter Loyalty, Persija Jakarta, The Jakmania. Keywords: Instagram, Digital Communication, Supporter Loyalty, Persija Jakarta, The Jakmania.